Ongoing symptomatic COVID-19 - practical advice: A review - Andrei A. Zaitsev; Igor' V. Leshchenko (ZAO "Consilium Medicum", 2022)
Studying the consequences of COVID-19 is a global priority in various countries around the world. The term long-covid or ongoing symptomatic COVID-19 should include situations with clinical manifestations of the disease lasting more than 4 but less than 12 weeks from the onset of the disease. The most urgent problem today remains the management of patients with persistent symptoms of past COVID-19.